2022
DOI: 10.1111/eci.13872
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pan‐immune‐inflammation value with other inflammation markers of long‐term survival afterST‐segment elevation myocardial infarction

Abstract: Background Atherosclerosis is a process that causes coronary artery disease and is associated with the inflammatory response. In this study, we aimed to evaluate the association of Pan‐Immune‐Inflammation Value (PIV) with in‐hospital and long‐term mortality in STEMI patients. Methods A total of 658 patients who were admitted to the emergency department of two tertiary centers with the diagnosis of STEMI and underwent percutaneous coronary intervention (PCI) between 2018 and 2022 were retrospectively enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
0
32
1
Order By: Relevance
“…Pan-immune-in ammation value is a newly used scoring system that includes neutrophil, monocyte, lymphocyte, and platelet counts and is often used to evaluate the association between tumor-mediated in ammation-immune response and survival [8,12]. Studies have investigated the relationship between PIV and various in ammatory conditions, including long-term survival after myocardial infarction, frailty (a geriatric syndrome), and diagnosis and prognosis in rheumatological diseases [7,[9][10][11]. Results from previous studies but not all reported that patients with high PIV levels measured at the onset of the condition considered indexed have a signi cantly increased likelihood of poor prognosis, treatment nonresponse and poor outcomes compared to those with low PIV levels [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pan-immune-in ammation value is a newly used scoring system that includes neutrophil, monocyte, lymphocyte, and platelet counts and is often used to evaluate the association between tumor-mediated in ammation-immune response and survival [8,12]. Studies have investigated the relationship between PIV and various in ammatory conditions, including long-term survival after myocardial infarction, frailty (a geriatric syndrome), and diagnosis and prognosis in rheumatological diseases [7,[9][10][11]. Results from previous studies but not all reported that patients with high PIV levels measured at the onset of the condition considered indexed have a signi cantly increased likelihood of poor prognosis, treatment nonresponse and poor outcomes compared to those with low PIV levels [12].…”
Section: Discussionmentioning
confidence: 99%
“…These scores typically comprise of pro-in ammatory cells, including neutrophils, platelets, monocytes, and lymphocytes. The pan-immune-in ammation value (PIV), which is mostly and recently used in clinical trials in cancer, rheumatological diseases, and other in ammatory processes; has not been adequately studied as a predictive marker for worse outcomes and prognosis in immunosuppressed patients [7][8][9][10][11]. Studies have generally found that elevated PIV levels are an indicator of worse scenario [7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it encompasses all major immune cells, PIV is considered the global quanti er of the cellular compartment of systemic in ammation (Fucà et al, 2020). The PIV values predicted mortality in ST-elevation myocardial infarction (STEMI) (Murat et al, 2023), end-stage renal disease (ESRD) (Zhang et al, 2023), and hepatic steatosis (Demiröz Taşolar and Çiftçi, 2022). However, PIV levels in patients with diabetes mellitus and metabolic syndrome and their association with IR have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…12 PIV was initially developed for the prognostic stratification of patients with advanced colorectal cancer, and further developed as a promising prognostic tool in a variety of solid tumors and in other inflammation-and immune-related diseases. [12][13][14][15][16][17][18][19] PIV has also been preliminarily investigated as a biomarker in BC patients 18,20 ; however, no data are available about the potential prognostic significance of PIV in aTNBC patients.…”
Section: Introductionmentioning
confidence: 99%